2013
DOI: 10.1371/journal.pone.0065159
|View full text |Cite
|
Sign up to set email alerts
|

Empathy as a Function of Clinical Exposure - Reading Emotion in the Eyes

Abstract: BackgroundEvidence based largely on self-report data suggests that factors associated with medical education erode the critical human quality of empathy. These reports have caused serious concern among medical educators and clinicians and have led to changes in medical curricula around the world. This study aims to provide a more objective index of possible changes in empathy across the spectrum of clinical exposure, by using a behavioural test of empathic accuracy in addition to self-report questionnaires. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
54
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 33 publications
7
54
0
1
Order By: Relevance
“…Importantly our scores are not only in line with previously published data but also concur with a more recent study conducted among medical students in Australia 14 , 29. The study done in Australia also found no difference among different years of training; in this study there was also no difference in RMET scores between medical students and a group of older more experienced physicians who were also surveyed.…”
Section: Discussionsupporting
confidence: 93%
“…Importantly our scores are not only in line with previously published data but also concur with a more recent study conducted among medical students in Australia 14 , 29. The study done in Australia also found no difference among different years of training; in this study there was also no difference in RMET scores between medical students and a group of older more experienced physicians who were also surveyed.…”
Section: Discussionsupporting
confidence: 93%
“…First, the sample size is small compared with those of recent work that has examined changes in empathy over time during medical training as assessed by the JSPE, as well as its factor validity . However, this sample size is comparable with those in much of the other longitudinal research on changes in empathy over the course of medical school, and this is the first study, to the present authors’ knowledge, to assess and compare empathy changes in medical students as assessed by the JSPE, or empathy in the context of the physician–patient interaction, and by a more general measure of students’ capacity for empathy, the QCAE, along with measures designed to assess the behavioural manifestation of this capacity. Additionally, there may be potential bias as a result of the self‐selection of participants in that patterns of change may be different in students who did not volunteer for the study.…”
Section: Discussionmentioning
confidence: 85%
“…Recent work failed to find changes in empathy during medical school or found declines in only some aspects of empathy and none in others . There is some evidence for increases in behavioural aspects of empathy . This suggests that empathy changes during medical training may be more complex than can be represented by an overall decline.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations